Synthesis of Co‐Doped MoS2 Monolayers with Enhanced Valley Splitting. Issue 11 (6th February 2020) - Zhou, Jiadong; Lin, Junhao; Sims, Hunter; Jiang, Chongyun; Cong, Chunxiao; Brehm, John A.; Zhang, Zhaowei; Niu, Lin; Chen, Yu; Zhou, Yao; Wang, Yanlong; Liu, Fucai; et al.
Abstract: Internal magnetic moments induced by magnetic dopants in MoS2 monolayers are shown to serve as a new means to engineer valley Zeeman splitting (VZS). Specifically, successful synthesis of monolayer MoS2 doped with the magnetic element Co is reported, and the magnitude of the valley splitting is engineered by manipulating the dopant concentration. Valley splittings of 3.9, 5.2, and 6.15 meV at 7 T in Co‐doped MoS2 with Co concentrations of 0.8%, 1.7%, and 2.5%, respectively, are achieved as revealed by polarization‐resolved photoluminescence (PL) spectroscopy. Atomic‐resolution electron microscopy studies clearly identify the magnetic sites of Co substitution in the MoS2 lattice, forming two distinct types of configurations, namely isolated single dopants and tridopant clusters. Density functional theory (DFT) and model calculations reveal that the observed enhanced VZS arises from an internal magnetic field induced by the tridopant clusters, which couples to the spin, atomic orbital, and valley magnetic moment of carriers from the conduction and valence bands. The present study demonstrates a new method to control the valley pseudospin via magnetic dopants in layered semiconducting materials, paving the way toward magneto‐optical and spintronic devices. Abstract : The synthesis of a Co‐doped MoS2 monolayer with enhanced valley Zeeman splitting is reported. Valley splittings are revealed by polarization‐resolved photoluminescence spectroscopy. Atomic‐resolution electron microscopy studies clearly identify the magnetic sites of Co substitution in the MoS2 lattice. The enhanced valley Zeeman splitting is further demonstrated by density functional theory and model calculations.